2018
DOI: 10.1002/pi.5532
|View full text |Cite
|
Sign up to set email alerts
|

Stiff and hierarchical chain nature of atactic and stereoregular poly(substituted methylene)s

Abstract: In this study, we estimated the chain nature of atactic and stereoregular poly(substituted methylene)s containing a phenylmethoxy side chain at each main‐chain backbone carbon atom using synchrotron X‐ray scattering to understand the topological and conformational properties of these rigid polymers. The atactic poly(substituted methylene) showed a linear chain nature. Contrastingly, the stereoregular poly(substituted methylene) exhibited a random coil structure. © 2018 Society of Chemical Industry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(80 reference statements)
0
10
0
Order By: Relevance
“…These numbers suggest that the polycarbene backbones are highly extended rather than coiled, as recently described for atactic homopolymers of benzyl diazoacetate. 38 Note also that compared to the corresponding homopolymer segments, the block copolymer appears to have similar thermal stability in air up to ~260 °C (SI, Figure S26).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…These numbers suggest that the polycarbene backbones are highly extended rather than coiled, as recently described for atactic homopolymers of benzyl diazoacetate. 38 Note also that compared to the corresponding homopolymer segments, the block copolymer appears to have similar thermal stability in air up to ~260 °C (SI, Figure S26).…”
mentioning
confidence: 95%
“…The end-to-end distance of the fully stretched out block copolymers of DP ∼ 175 (based on Figure C and relative ratio of two blocks) is estimated to be 220 Å (“End-to-End Distance” section, SI), which translates to a d -spacing of 440 Å. These numbers suggest that the polycarbene backbones are highly extended rather than coiled, as recently described for atactic homopolymers of benzyl diazoacetate . Note also that compared to the corresponding homopolymer segments, the block copolymer appears to have similar thermal stability in air up to ∼260 °C (SI, Figure S26).…”
mentioning
confidence: 99%
“…Although it is an amorphous polymer, the peak corresponding to amorphous hallo provides insight into the packing structure. [ 41–43 ] The peak position in the lowest q range is 6.4 nm −1 , which corresponds to 0.98 nm. This reflects the cross‐sectional radius of the polymer chain, including the bulky side chain.…”
Section: Resultsmentioning
confidence: 99%
“… 47 Subsequent studies by Tokita, Shikinaka, Ihara, and co-workers confirmed that PEA and related syndiotactic polymers of diazoacetates show thermotropic liquid crystalline behavior due to a rod-like helical conformation in the polymer backbone. 48 50 The syndiotactic polymer pM 5 is likely to form similar triple helices, and the forces keeping the aggregates together are likely to be stronger in such triple-helix aggregates than in the atactic material, leading to a lower LCST for the syndiotactic polymer than for the atactic material ( Figure 6 , bottom). Solvation into individual polymer chains in solution is enthalpy-driven, while formation of aggregates at higher temperature is an entropy-driven process, releasing water solvent molecules upon aggregation of the individual solvated polymer chains.…”
Section: Resultsmentioning
confidence: 99%